Protective Effects of Plant Extracts on Oxidative Stress and Genetic Damage in Neonates Exposed to Toxic Agents - Paniagua-Pérez, Rogelio; Madrigal-Santillán, Eduardo O.; -González, Isela Álvarez; Madrigal-Bujaidar, Eduardo (Journal of Neonatal Surgery, 2025)
Oxidative stress is a key factor in the genesis of various neonatal pathologies, especially in those exposed to toxic agents. This study evaluates the protective potential of antioxidant-rich plant extracts against oxidative stress and genetic damage in neonates. A comprehensive review of the scientific literature of the last five years was conducted, focusing on studies that analyze the efficacy of these extracts in neonatal models. The results indicate that certain plant extracts have antioxidant properties that mitigate oxidative and genetic damage in neonates exposed to toxic agents, suggesting their potential therapeutic use in this vulnerable population. duces pain during local anesthesia administration in children compared to topical anesthetic. Its advantages include pain reduction, quicker application, and avoidance of unpleasant taste.